Icing on the cake: Can the top-floor units serve as a status good and an investment simultaneously? - Edward Chi Ho Tang; Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Situated atop condominium buildings, 'top floor units' (TFU) offer unparalleled views and privacy, courtesy of accessible roofs. This paper empirically examines this status symbol and finds that: (1) TFUs interact with the macroeconomy differently from ordinary units, (2) when considering the liquidity factor, TFUs should not be included in the portfolio, (3) the trade-off between holding period and annualized return for TFUs significantly differs from ordinary units, suggesting alternative investment strategies are employed for TFUs, and (4) the liquidity of the TFU segment is less stable than ordinary units, potentially deterring shortterm speculators.
Keywords: D10; G10; R21; 330; top floor units; peer group effect on consumption; speculation; submarkets; Markov switching model